HUBUNGAN PENGETAHUAN DAN USIA IBU TERHADAP PEMBERIAN ASI EKSKLUSIF - Darmawati, Junay; Lidya Fransisca; Adriani (LPPM STIKes Mitra Adiguna, 2024)
Exclusive breastfeeding for babies aged 0-6 months has a great contribution to the growth and development and immunity of babies which can help prevent various childhood diseases, especially gastric, airway and asthma disorders in children. The purpose of this study was to determine the relationship between maternal knowledge and age to exclusive breastfeeding. The research method used in this study is an analytical survey with a cross sectional approach. The population in this study is all mothers who have babies aged 7-12 months who visited RB Asri Palembang in 2023 with a research sample of 40 respondents taken using an accidental sampling technique. The results of the study were obtained from 40 respondents who gave exclusive breastfeeding as many as 21 respondents (52.5%) while mothers who did not give exclusive breastfeeding were 19 people (47.5%), mothers with good knowledge as many as 22 respondents (55.0%) while mothers with poor knowledge were 18 people (45.0%), and mothers with the age of 20-35 years as many as 21 people (52.5%) while mothers with the age of <20 years and >35 years were 19 people (47.5%). The results of the statistical test found that there was a meaningful relationship between maternal knowledge and age and exclusive breastfeeding at RB Asri Palembang in 2023.